ANALISIS TINGKAT DAYA SERAP ANGGARAN BELANJA DAERAH DI KOTA MALANG - Luluk Krisdiyanawati; M. Faisal Abdullah; Yunan Syaifullah (Program Studi Ekonomi Pembangunan, 2020)
The purpose of this research is to understand the level of absorptive capacity of regional expenditure budgets in Malang City and to understand the effect of planning variables, procurement of goods and services variables, and human sesource variables on the absorption of regional expenditure budgets in Malang. This type of research is quantitative research. The population in this research were 20 regional work units in Malang in the form of Agency and Department. The sample of this research is the Regional Financial and Asset Agency, Planning Research and Development Agency, Education and Culture Department, Health Department, and Environment Department in Malang City with respondents occupying positions related to the budget, namely the authority of budgets users, officials making commitments, the technical executive officer of the activity, the official signing the payment order, and the treasurer of the expenditure.The technical analysis used is multiple linear regression. The results of this research indicated that the human resources variable has a significant positive effect on the absorption of regional budgets. While the planning variable and the procurement of goods and services variable do not significantly positive influence the absorption capacity of the budget.